Challenges in the integration of quality and innovation management systems - Lopes, Ana (2022)
Seeking to reduce the number of inconsistencies in their processes, many organisations choose to implement the ISO 9001:2015 quality management standard. Their aim is to improve operational performance while, at the same time, they cope with increased pressures from the market to present innovative products and solutions and from the stakeholders to implement new organizational methods. This work intends to investigate how organisations can leverage ISO 9001:2015 in implementing the ISO 56002:2019 innovation management standard, given that both standards have a high degree of compatibility with each other. For that purpose, meetings were held with senior managers and quality managers of three Portuguese SMEs to discuss the existing potential challenges and gaps in the integration of both management systems. The results point to the existence of a significant set of practices in the field of quality that can support and facilitate the formalization of integrated management systems. Nevertheless, generalization of the results should be avoided, and more research is needed, since the integration of management systems is often conditioned by cost and time related issues. Furthermore, it is disputable whether a company can simultaneously reach a high level of efficiency (brought about by implementing a quality management system) and a high level of innovation (made possible by the implementation of an innovation management system) thus jeopardizing the implementation of an integrated management system.